Enhanced Immune Responses and Protective Immunity to Zika Virus Induced by a DNA Vaccine Encoding a Chimeric NS1 Fused With Type 1 Herpes Virus gD Protein - Pereira, Lennon Ramos; Alves, Rúbens Prince dos Santos; Sales, Natiely Silva; Andreata-Santos, Robert; Venceslau-Carvalho, Aléxia Adrianne; Pereira, Samuel Santos; Castro-Amarante, Maria Fernanda; Rodrigues-Jesus, Mônica Josiane; Favaro, Marianna Teixeira de Pinho; Chura-Chambi, Rosa Maria; Morganti, Ligia; Ferreira, Luís Carlos de Souza (Frontiers in Medical Technology, 2020)
Zika virus (ZIKV) is a globally-distributed flavivirus transmitted to humans by Aedes mosquitoes, usually causing mild symptoms that may evolve to severe conditions, including neurological alterations, such as neonatal microcephaly and Guillain-Barré syndrome. Due to the absence of specific and effective preventive methods, we designed a new subunit vaccine based on a DNA vector (pgDNS1-ZIKV) encoding the non-structural protein 1 (NS1) genetically fused to the Herpes Simplex Virus (HSV) glycoprotein D (gD) protein. Recombinant plasmids were replicated in Escherichia coli and the expression of the target protein was confirmed in transfected HEK293 cells. C57BL/6 and AB6 (IFNAR1–/–) mice were i.m. immunized by electroporation in order to evaluate pgDNS1-ZIKV immunogenicity. After two doses, high NS1-specific IgG antibody titers were measured in serum samples collected from pgDNS1-ZIKV-immunized mice. The NS1-specific antibodies were capable to bind the native protein expressed in infected mammalian cells. Immunization with pgDNS1-ZIKV increased both humoral and cellular immune responses regarding mice immunized with a ZIKV NS1 encoding vaccine. Immunization with pgDNS1-ZIKV reduced viremia and morbidity scores leading to enhanced survival of immunodeficient AB6 mice challenged with a lethal virus load. These results give support to the use of ZIKV NS1 as a target antigen and further demonstrate the relevant adjuvant effects of HSV-1 gD.